Drivers and barriers to rural and urban healthcare placement in Ghana: a Delphi study - Boye, Bernard Okoe; Pokhrel, Subhash; Cheung, Kei Long; Anokye, Nana (Frontiers in Public Health, 2025)
ObjectiveThis study explored the level of consensus on the drivers and barriers influencing doctors’ decisions to work in rural versus urban areas. The study provides insights into systemic issues affecting healthcare workforce distribution in Ghana. Access to medical care is particularly important given the changing demographics of Ghana, including the growth of the older and chronically ill population and the high proportion of older adults living in rural areas.MethodsA three-round e-Delphi study was conducted among doctors and regional directors of the Ghana Health Service using a seven-point Likert scale. A median score of ≥6 and an interquartile range of ≤1 was used as cutoffs. In total, 47 experts participated in the study. Although 55 initially registered interest, only 47 took part in the first round. By the second and third rounds, 42 experts remained engaged in the study.ResultsExperts reached consensus on 40 descriptors (78%), of which 37 (93%) were considered important. Doctors reached consensus on 11 and 7 important drivers and barriers of rural incentive adoption, respectively, while reaching consensus on 8 important drivers of urban incentive factors. Regional directors reached consensus on 4 and 7 important drivers of rural and urban factors, respectively. Four categorical themes emerged from the analysis. These are financial, professional development and career advancement, work-life balance, and community lifestyle factors.ConclusionThe contrast in drivers and barriers between rural and urban healthcare workers necessitates tailored policy approaches, resource allocation strategies, and workforce planning efforts to ensure equitable access and quality care across diverse settings and among different sub-populations, especially the growing number of aged and chronically ill.